PERKEMBANGAN BATERAI DAN CHARGER UNTUK MENDUKUNG PEMASYARAKATAN SEPEDA LISTRIK DI INDONESIA - Wijaya, N. M. A.; Kumara, I. N. S.; Divayana, Y. (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p3, 2021)
Nowadays electric vehicles begin to grow and are supported by improved battery technology such as smaller size and capable of storing large amounts of energy. One type of simple electric vehicle is an electric bicycle. This paper reviews the availability of batteries and battery chargers for electric bicycles in Indonesia. The review includes a discussion on the technical specifications, manufacturer, the vendor of the battery, and battery charger. The survey produced a data consists of 117 batteries and 54 chargers and then processed to obtain status on the availability in the domestic market. The information regarding the availability of batteries and battery chargers for electric bicycles is expected to be used as a quick reference for the community in choosing batteries and battery chargers for electric bicycles and can provide an overview to stakeholders about the status of batteries and chargers in conducting research and development of batteries and charging equipment for electric vehicles.